Hidradenitis suppurativa - current and promising non-surgical treatment - Natalia Baran; Klaudia Bogusz; Marcela Maksymowicz; Adriana Bielak; Aleksandra Nowak; Łucja Cywka; Weronika Szwed; Alicja Nowak; Piotr Machowiec (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Hidradenitis suppurativa (HS) also known as acne inversa is a chronic, inflammatory dermatosis with predilection to apocrine gland-rich regions. It is a multifactorial disease in which genetic and environmental factors play a key role. In this paper, we provide an overview of the current knowledge in most commonly used and emerging  treatment options of HS.